Clinical trials and drug cost savings for Italian health service - Francesca D'Ambrosio; Gianfranco De Feo; Gerardo Botti; Arturo Capasso; Sandro Pignata; Piera Maiolino; Maria Triassi; Antonio Nardone; Franco Perrone; Michela Piezzo; Antonio Maria Grimaldi; Ida Palazzo; et al. (BMC, 2020)
Abstract Background The cost of anticancer drugs is constantly growing. The aim of this study was determine the impact in terms of cost reduction for anticancer drug in the Italian Health Service due to patient participation in clinical trials. Methods We evaluated the cost of drugs administered to patients treated in clinical trials at the National Cancer Institute of Naples in a four-week time period. Patients with a diagnosis of different cancers were considered, including adjuvant therapy and treatment for advanced disease, pharma sponsored and investigator initiated phase I, II and III clinical studies. We defined the expected standard treatment for each patient and we calculated the cost of the standard antineoplastic drugs that should be administered in clinical practice outside clinical trials. We used the market price of drugs to determine the cost savings value. Costs other than drugs were not included in the cost saving calculation. Results From 23.10.2017 to 17.11.2017, 126 patients were treated in 34 pharma sponsored and investigator initiated clinical trials, using experimental drugs provided free of charge by the sponsors, for an overall number of 152 cycles of therapy. If these patients were treated with conventional therapies in clinical practice the cost of antineoplastic drugs would account for 517,658 Euros, with an average of 5487 Euros saved per patients for a period of 4 weeks. Conclusions Clinical trials with investigational antineoplastic drugs provided free of charge by Sponsors render considerable cost savings, with a tangible benefit in clinical and administrative strategies to reduce drug expenditures.